Toxicity effects in zebrafish embryos (Danio rerio) induced by prothioconazole. (December 2019) - Tian, Sinuo; Teng, Miaomiao; Meng, Zhiyuan; Yan, Sen; Jia, Ming; Li, Ruisheng; Liu, Li; Yan, Jin; Zhou, Zhiqiang; Zhu, Wentao
Abstract: Triazole fungicides are widely used in agriculture production and have adverse impacts on aquatic organisms. As one of the triazole fungicides, prothioconazole has been reported to cause many toxicological effects, but its risks to aquatic organisms are unknown. In this study, we systematically explored the toxicity effects of prothioconazole exposure on zebrafish embryos ( Danio rerio ) involving in developmental toxicity, oxidative damage and metabolism disorders. The results showed that prothioconazole exposure to zebrafish embryos produced a series of toxic symptoms, including hatching inhibition, shortening of body length, pericardial cyst and yolk cyst . In addition, prothioconazole exposure caused significant lipid peroxidation and oxidative damage. Particularly, we also found that metabolites and genes involved in lipid metabolism also showed significant changes. This study may provide theoretical basis for systematically assessing the potential risks of zebrafish embryos with prothioconazole exposure. Graphical abstract: Image 1 Highlights: Prothioconazole had developmental toxicity to zebrafish embryos. Prothioconazole exposure caused lipid peroxidation and induced oxidative damage. Prothioconazole disturbed metabolism profiles of zebrafish larvae. Prothioconazole affected the genes involved in lipid metabolism. Abstract : In this study, we found that prothioconazole could induce oxidative damage and metabolism disorders of zebrafish embryos.